Common ownership in the US pharmaceutical industry: A network analysis - Albert Banal-Esta\~nol; Melissa Newham; Jo Seldeslachts (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We investigate patterns in common ownership networks between firms that are active in the US pharmaceutical industry for the period 2004-2014. Our main findings are that "brand firms" - i.e. firms that have R&D capabilities and launch new drugs - exhibit relatively dense common ownership networks with each other that further increase significantly in density over time, whereas the network of "generic firms" - i.e. firms that primarily specialize in developing and launching generic drugs - is much sparser and stays that way over the span of our sample. Finally, when considering the common ownership links between brands firms, on the one hand, and generic firms, on the other, we find that brand firms have become more connected to generic firms over time. We discuss the potential antitrust implications of these findings.
Keywords: G23; K21; L11; L41; L65; 330; Common ownership networks; pharmaceutical companies; competition; innovation